Exchange Rate Movements and International Interdependence of Stock Markets. (IMF Working Papers; Working Paper ;, 1989)
This paper investigates linkages between stock markets in seven industrialized countries since 1974. Empirical evidence shows that both nominal and real stock prices (and returns) are strongly positively correlated across countries, and that nominal exchange rate changes do not have systematic effects on nominal stock prices. A two-country theoretical model is developed and an attempt is made to reconcile the empirical findings with the properties of this model. Independent evidence on the main sources of shocks is used to argue that the time-varying correlation in the data can be reconciled with the predictions of the theory.